Biphasic Liquid-Liquid Extraction of Biosurfactant from Lactobacillus delbrueckii - Surbhi Goyal; Jagdish Singh (Brazilian Archives of Biology and Technology, 2022)
Abstract: The present work is focused mainly on optimizing the extraction of glycoprotein- biosurfactant (BS) produced by Lactobacillus delbrueckii in a biphasic liquid-liquid extraction. The production yield of BS is significantly affected by extraction strategies instead of the whole fermentation process, so it becomes a straightforward approach to enhance BS yield while optimizing various extraction parameters. The tailoring of process parameters for BS extraction was achieved by OFAT (one factor at a time) strategy and partition coefficient (Kd) served as the calculation factor for extraction. The optimal yield of BS (5+0.1 g/L) from CFB (from cell-free broth) was achieved by solvents; chloroform, methanol, and, butanol, 1:2:1 (v/v), from cell-free broth (CFB), 30% (v/v), at pH 3.5, temperature 37°C after extraction time of 60 min. Under optimized conditions, the extraction yield was 78.5% higher and subsequently, a co-current, and counter-current system enhanced the extraction yield by 16% (5.8g/L) and 20% (6.0g/L) respectively. The purity of extracted BS (EBS) was confirmed by UV/Visible spectroscopy and HPLC (High-performance liquid chromatography). The concentration-dependent activity profile of EBS analyzed by ODA (oil displacement area; 50.24+0.3 cm2), DCD (drop collapse diameter; 1.1+0.3 cm), and EI24 (73+0.3%), exhibited enhancement by 60, 52, and 55% respectively as compared to control. Thin-layer chromatography (TLC), FTIR (Fourier Transform Infra-Red) and NMR (Nuclear Magnetic Resonance) techniques confirmed the polymeric glycoprotein (65:35 protein: carbohydrates %) nature of BS.